New therapeutic strategies in HCV: second‐generation protease inhibitors. (3rd January 2013) - Clark, Virginia C.; Peter, Joy A.; Nelson, David R.
Abstract: Telaprevir and boceprevir are the first direct‐acting antiviral agents approved for use in HCV treatment and represent a significant advance in HCV therapy. However, these first‐generation drugs also have significant limitations related to thrice‐daily dosing, clinically challenging side‐effect profiles, low barriers to resistance and a lack of pan‐genotype activity. A second wave of protease inhibitors are in phase II and III trials and promise to provide a drug regimen with a better dosing schedule and improved tolerance. These second‐wave protease inhibitors will probably be approved in combination with PEG‐IFN and Ribavirin (RBV), as well as future all‐oral regimens. The true second‐generation protease inhibitors are in earlier stages of development and efficacy data are anxiously awaited as they may provide pan‐genotypic antiviral activity and a high genetic barrier to resistance.